Effect of Terbuthylazine-2-hydroxy at Environmental Concentrations on Early Life Stages of Common Carp (Cyprinus carpio L.). (6th February 2014) - Velisek, Josef; Stara, Alzbeta; Koutnik, Dalibor; Machova, Jana
Abstract : The aim of the study was to investigate effects of the triazine's herbicide terbuthylazine-2-hydroxy on early life stage of common carp ( Cyprinus carpio L.) through antioxidant indices, mortality, growth, development, and histopathology. Based on accumulated mortality in the experimental groups, lethal concentrations of terbuthylazine-2-hydroxy were estimated at 35-day LC50 = 10.9 mg/L terbuthylazine-2-hydroxy. By day 15, fish were exposed to 3.5 mg/L and by day 26, fish were exposed to 0.0029 mg/L; real environmental concentration in Czech rivers, 0.07 mg/L, 1.4 mg/L, and 3.5 mg/L terbuthylazine-2-hydroxy, showed significantly lower mass and total length compared with controls. Based on inhibition of growth in the experimental groups, lowest observed effect concentration (LOEC) = 0.002 mg/L terbuthylazine-2-hydroxy and no observed effect concentration (NOEC) = 0.0001 mg/L terbuthylazine-2-hydroxy. No significant negative effects on hatching or embryo viability were demonstrated at the concentrations tested, but significant differences in early ontogeny among groups were noted. Fish from the two highest tested concentrations showed a dose-related delay in development compared with the controls. Total superoxide dismutase (SOD) activity was significant lower in all groups testedly for terbuthylazine-2-hydroxy compared with the control group. At concentrations of 1.4 and 3.5 mg/L damage to caudal kidney tubules when compared to control fish was found.